GENDER PROBLEMS IN THE NOVELS «A LITTLE DRAMA» BY V. PIDMOHYLNY AND «LADY CHATTERLEY’S LOVER» BY D. LAWRENCE - Девдюк I. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is devoted to the comparative analysis of gender problems in the novels “A Little Drama” by V. Pidmohylny and “Lady Chatterley’s Lover” by D. Lawrence. The key common component of the works is the love discourse, in the plane of which philosophical, moral and ethical, national concepts are realized, the genre-compositional paradigm is outlined, marked by gender markers. The gender aspect is actualized in the images of the main heroines, the common feature of which is the desire to achieve independence and internal freedom, and then, to go beyond the traditional gender stereotypes.